Energy, hierarchy and the origin of inequality - Blair Fix (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2018)
Where should we look to understand the origin of inequality? Most research focuses on three windows of evidence: (1) the archaeological record; (2) existing traditional societies; and (3) the historical record. I propose a fourth window of evidence - modern society itself. I hypothesize that we can infer the origin of inequality from the modern relation between energy use, hierarchy, and inequality. To do this, I create a large-scale numerical model that is informed by modern evidence. I then use this model to project modern trends into the past. The results are promising. The model predicts an explosion of inequality with the transition to agrarian levels of energy use. Subsequent increases in energy use are predicted to have little effect on inequality. The results are broadly consistent with the available evidence. This suggests that the hierarchical structure of modern societies may provide a window into the origin of inequality.
Keywords: 330; origin of inequality; hierarchy; energy; institution size; numerical model; function; coercion